Development, Swarming, Colony Orphaning And Fly Parasitism In Subterranean Termites, Macrotermes Gilvus (Hagen) And Macrotermes Carbonarius (Hagen) (Blattodae: Termitidae) - Neoh, Kok Boon (2010)
The present research provides insight into termite's caste developmental pathways, population biology, colony breeding structures and community ecology. Kajian ini memberi pemahaman mengenai tapak jalan perkembangan kasta anai-anai, biologi populasi, struktur pembiakan koloni dan ekologi komuniti.